2021
DOI: 10.1016/j.eclinm.2020.100681
|View full text |Cite
|
Sign up to set email alerts
|

Association of carbonated soft drink and fast food intake with stress-related sleep disturbance among adolescents: A global perspective from 64 countries

Abstract: Background Poor quality sleep adversely impacts on adolescent wellbeing. More multinational research is needed to understand modifiable risk factors, such as dietary behaviours. This study aimed to examine the association of carbonated soft drink and fast food intake with stress-related sleep disturbance among adolescents across 64 countries. Methods We analysed the Global School-based Student Health Survey data from 175,261 adolescents (mean age 13.8 [0.98]; 48.5% fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(52 reference statements)
2
10
0
1
Order By: Relevance
“…Answer options were: never, sometimes, most of the time, and always. Consistent with previous research (38,40,41), participants who answered "most of the time" or "always" were considered to have sleep disturbance in this study.…”
Section: Sleep Disturbancesupporting
confidence: 69%
“…Answer options were: never, sometimes, most of the time, and always. Consistent with previous research (38,40,41), participants who answered "most of the time" or "always" were considered to have sleep disturbance in this study.…”
Section: Sleep Disturbancesupporting
confidence: 69%
“…Linear regression adjusted for gender, self-reported skin color, age, socioeconomic score, consumption of fresh and minimally processed foods (in grams), consumption of processed foods (in grams), total energy consumed, physical activity, z score of body mass index, smoking and alcohol consumption. who met recommended sleep hours, consistent with the ndings of previous studies [6,[12][13][14][21][22][23]. Sleep duration can impact the quality of life, as adequate sleep duration is essential for the full development of adolescents.…”
supporting
confidence: 88%
“…It is possible to prevent this unusual mortality by changing lifestyle and food habits, such as not smoking, a healthy diet, controlling obesity, and exercising more. The study found a strong correlation between fast food habits and stress-related sleep disturbances [4]. Many cardiovascular disorders are associated with unhealthy dietary behaviors.…”
Section: Introductionmentioning
confidence: 77%